Pembuatan Bahan Ajar Digital Mata Pelajaran Akuntansi Dasar Kelas X Pada SMK Kartini Batam - Ria Karina; Jeksen Jeksen (Universitas Internasional Batam, 2021)
This research was conducted by author to make digital teaching materials for basic accounting subjects that are in accordance with the school curriculum so that they can be used in the future. SMK Kartini Batam usually used modules as classroom learning materials. This practical work activity was carried out from 25 September 2020 - 20 January 2021. The author used the method of observation, interviews and documentation in the implementation of this practical work. In the problems that occur, the authors designed digital teaching materials for basic accounting subjects using PowerPoint and the Powtoon application as an interesting learning video in order to facilitate students understanding in learning and make it easier for teachers in teaching activities.